Multi-scale spatiotemporal pattern and its causes of meteorological drought over a typical steppe in the Inner Mongolia Plateau - Yixuan Wang; Shuyue Shi; Tingxi Liu; Limin Duan; Jianguo Ji; Shiyu Zhang (Journal of Hydrology: Regional Studies, 2025)
Study region: Against the backdrop of intensifying climate change, extreme drought events have become increasingly frequent in arid and semi-arid grasslands, posing significant threats to ecological security and sustainable development. This study focused on a typical steppe in the eastern Inner Mongolia Plateau. Study focus: Based on the Standardized Precipitation Index, the spatiotemporal evolution of meteorological drought across multiple scales was analyzed through principal component analysis and time-varying moment model. Furthermore, the influences of atmospheric circulations on regional drought variabilities were elucidated using covariate-incorporated modeling. New hydrological insights for the region: The results reveal the pronounced spatial heterogeneity in droughts across the study area, which can be categorized into three distinct sub-regions, including a western sub-region characterized by moderate drought, a southeastern sub-region prone to severe droughts, and a northeastern sub-region susceptible to extreme droughts. Temporally, a significant linear trend in droughts was observed in the western sub-region, primarily marked by the aggravation of droughts in summer and the alleviation of droughts in the non-growing season. Drought dynamics in the southeastern sub-region were mainly manifested as the linear extremization in summer and the nonlinear alleviation in the non-growing season. In the northeastern sub-region, drought conditions remained relatively stable overall, but showed a trend toward extreme drought during the growing season. The most dominant atmospheric circulation drivers were identified as the North Atlantic Oscillation (NAO), the Pacific-North American Oscillation (PNA), and the Southern Oscillation (SO). Specifically, both the positive phase of NAO and the negative phase of PNA contributed to the aggravation of regional drought, while the positive and negative phases of SO respectively exacerbated droughts in the western and eastern regions. These findings provide a theoretical reference for enhancing the accuracy of drought prediction and advancing risk management strategies in grassland ecosystems.